The future of African wild fruits – a drive towards responsible production and consumption of the marula fruit - Hlangwani, Edwin; Hal, Penny Hiwilepo-van; Moganedi, Kgabo L. M.; Dlamini, Bhekisisa C. (Frontiers in Sustainable Food Systems, 2023)
The marula fruit has played a central role in the dietary intake, socioeconomic standing, and cultural practices of communities in southern Africa for over 10,000 years. The marula fruit is rich in nutritional compounds such as vitamins, minerals, organic acids, and amino acids which contribute to the health properties of the final products. These products can be sold informally by locals or developed into commercially viable, export products. The recent domestic and international demand for marula fruit-based products has raised sustainability concerns such as over-harvesting, habitat destruction, and unsustainable production practices. Given these challenges, a responsible and inclusive approach to marula production and consumption is required to meet the nutritional needs and sustainably contribute to the socioeconomic development of these communities. As a result, a scoping review approach was used to map out the literature on the production and consumption of the marula fruit. All reviewed literature explicitly focused on the marula fruit, the responsible use of the marula fruit, and sustainability practices in the production and consumption of marula fruit-based products. Furthermore, this review examined the potential benefits and challenges of expanding the production and consumption of marula products and identified strategies for promoting sustainable practices and equitable distribution of benefits. Despite the challenges in pre-and-postharvest processing, the marula fruit has remained a valuable resource. Thus, the sustainable production and consumption of the marula fruit require a holistic approach that addresses these challenges and promotes sustainable practices and equitable distribution of benefits. Central to this approach is the application of various technologies to establish robust value chains so the marula fruit industry can thrive.